The potential role of prophylactic/functional knee bracing in preventing knee ligament injury - Rishiraj, N.; Taunton, J. E.; Lloyd-Smith, R.; Woollard, R.; Regan, W.; Clement, D. B. (Sports Medicine, 2009)
It is estimated that knee injuries account for up to 60% of all sport injuries, with the anterior cruciate ligament (ACL) accounting for almost half of these knee injuries. These knee injuries can result in high healthcare costs, as an ACL injury is often associated with surgery, long and costly rehabilitation, differing degrees of impairment and potential long-term consequences such as osteoarthritis. The interest in ACL injury prevention has been extensive for the past decade. Over this period, many ACL (intrinsic and extrinsic) injury risk factors have been identified and investigated by numerous researchers. Although prevention programmes have shown potential in decreasing knee ligament injuries, several researchers have suggested that no conclusive evidence has been presented in reducing the rate and/or severity of ACL injuries during sporting competition. Knee braces have been available for the last 30 years and have been used to assist individuals with ACL-deficient and ACL-reconstructed knees. However, research is limited on the use of knee braces (prophylactic and functional) to potentially prevent knee ligament injury in the non-injured population. One possible explanation for the limited research could be that the use of these devices has raised concerns of decreased or impaired athletic performance. In summary, the review of subjective and some objective publications suggests that a functional knee brace may offer stability to an ACL-deficient knee joint; however, research is limited on the use of a knee brace for prophylactic use in non-injured athletes. The limited research could be a result of fear of performance hindrance that has led to poor knee brace compliance.